1998
DOI: 10.1001/archinte.158.13.1450
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Cardiac Decision Making

Abstract: Participants identified common issues influencing health care decision making, regardless of race. However, additional factors were expressed only by African American participants. These factors conveyed racial differences in perceptions of the health care system that may, in part, contribute to differences in health care decision making and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…17,36 Mistrust and perceived discrimination may contribute to differences in health care decision making and pursuit of care. 37 These perceptions may be justified, as studies have shown that faced with identical scenarios, physicians prescribe different diagnostic and treatment regimens to patients based on race. 13 Current problems with low Medicaid reimbursements and provider nonparticipation may play a role in minorities receiving less care in outpatient settings, as minorities depend in greater proportion on Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…17,36 Mistrust and perceived discrimination may contribute to differences in health care decision making and pursuit of care. 37 These perceptions may be justified, as studies have shown that faced with identical scenarios, physicians prescribe different diagnostic and treatment regimens to patients based on race. 13 Current problems with low Medicaid reimbursements and provider nonparticipation may play a role in minorities receiving less care in outpatient settings, as minorities depend in greater proportion on Medicaid.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there may be areas in which existing confirmed concepts can be enriched in the future. For example, involvement of family and friends in decision-making processes may be an important addition to the decision-making concept (Ferguson, Weinberger, Westmoreland, et al 1998;Riehman, Sly, Soler, et al 1998). Further modifications and final specification of the scales and framework should be based on additional validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about factors that influence patient decision-making in ischemic heart disease, as well as whether racial groups differ in regard to these factors. To advance knowledge in these areas, Ferguson and colleagues 88 conducted a study using 15 focus groups with black and white patients who had received treatment for ischemic heart disease in 1 of 2 university-affiliated hospital emergency …”
Section: Equitymentioning
confidence: 99%